Epigallocatechin gallate prevents senescence by alleviating oxidative stress and inflammation in WI-38 human embryonic fibroblasts. Issue 46 (27th August 2019) - Zhang, Qiao; Wu, Yuqing; Guan, Yue; Ling, Fan; Li, Ying; Niu, Yucun
Abstract : Increased levels of oxidative stress and inflammation are the underlying mechanisms behind the aging process and age-related diseases. Abstract : Increased levels of oxidative stress and inflammation are the underlying mechanisms behind the aging process and age-related diseases. The purpose of our research is to explore whether epigallocatechin gallate (EGCG) can extend replicative life span by preventing the oxidative stress and inflammatory effects of WI-38 fibroblasts and the involved mechanisms in vitro . WI-38 cells were treated with different concentrations of EGCG (0, 25, 50 and 100 μM) at population doubling (PD) 25. At late-stage cells, we determined the age-associated genes with signaling through transcriptome sequencing. The expression profile of the targets in WI-38 fibroblasts was confirmed by bioinformatics analysis, qPCR and western blot. We found that EGCG markedly decreased reactive oxygen species (ROS), and inflammation factors, tumor necrosis factor-α (TNF-α), interleukin (IL)-6, and significantly increased cell proliferation at PD 35 and 45. EGCG treatments significantly decreased p53 and retinoblastoma (Rb) expressions, markedly increased p-Rb and E2F2 expressions as well as antioxidant enzymes and superoxide dismutase (SOD) 1 and SOD2 content, and obviously decreased the expressions of inflammation factors IL-32, TNF-α expressions at PD 45 WI-38 cells. Moreover, the effects were changed by EGCG treatment by p53 siRNA or overexpression. These findings in our studies reveal that EGCG treatments improved senescence and enhanced the replicative life span through alleviating oxidative stress and inflammation in WI-38 fibroblasts.